2020
DOI: 10.1049/iet-sen.2019.0128
|View full text |Cite
|
Sign up to set email alerts
|

Toward successful agile requirements change management process in global software development: a client–vendor analysis

Abstract: Requirements change management (RCM) is an important and complicated phase in the agile for the software development process. The objective of this study was to identify and analyse the factors that can positively affect the agile RCM (ARCM) process in the context of global software development (GSD). To this end, a questionnaire survey was carried out with researcher and practitioner participants working in the field of GSD. From the 56 survey respondents, a total of 20 factors that can positively influence t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 44 publications
0
26
0
1
Order By: Relevance
“…One possible threat towards the validity of this paper is that, due to the limited time and resources, the sample size of the survey questionnaire ( n = 123) might not be strong enough to justify the validity of the reported factors. However, based on different other existing studies [33, 35, 65, 66 ], this is a representative sample to justify the results and discussion of this study.…”
Section: Limitations Of the Studymentioning
confidence: 90%
See 1 more Smart Citation
“…One possible threat towards the validity of this paper is that, due to the limited time and resources, the sample size of the survey questionnaire ( n = 123) might not be strong enough to justify the validity of the reported factors. However, based on different other existing studies [33, 35, 65, 66 ], this is a representative sample to justify the results and discussion of this study.…”
Section: Limitations Of the Studymentioning
confidence: 90%
“…There might be a possible threat towards the validity of the SFs mapping process into Ramasubbu [64 ] framework categorises, as we used the informal scaling approach. However, our mapping process is justifiable by considering the same mapping process used in other studies [15, 20, 65 ].…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Lack of control at overseas sites [2], [5] Ch15 Asymmetry in processes, policies, and standards [3], [7], [11]…”
Section: Ch14mentioning
confidence: 99%
“…Global Software Development (GSD) is a "plan of action in which the knowledge workers preform the software development activities beyond the geographical, cultural and temporal boundaries" [1]. Software industry adopts GSD as it offers access to skilled human resources at a relatively low cost [2,3]. For example, Khan et al [4] indicated that GSD costs less than one third in developing countries compared with developed countries.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the importance of RCM in the GSD environment, little empirical research has been conducted to address the problems faced by the practitioners. Lai and Ali, 17 Ramzan and Ikram, 52 Akbar et al, 53 Kamal et al, 54 and Shafiq et al 1 underlined that less effort had been directed towards developing the RCM tools and techniques in the GSD context. Anwer et al 55 mentioned that eight out of 10 software firms working in GSD faced RCM problems owing to poor planning and ineffective RCM standards and tools.…”
Section: Literature Review and Motivationmentioning
confidence: 99%